Valuation of digital platforms: Experimental evidence for Google and Facebook - Bodo Herzog (International Journal of Financial Studies, 2018)
This article investigates the fundamental value of digital platforms, such as Facebook and Google. Despite the transformative nature of digital technologies, it is challenging to value digital services, given that the usage is free of charge. Applying the methodology of discrete choice experiments, we estimated the value of digital free goods. For the first time in the literature, we obtained data for the willingness-to-pay and willingness-to-accept, together with socio-economic variables. The customer's valuation of free digital services is on average, for Google, 121 exteuro per week and Facebook, 28 exteuro.
Keywords: C82; I30; O40; 330; digital platform; free goods; choice experiment; two-sided markets